Strategi Pemuridan dalam Pembinaan Spiritualitas ASN Kristiani - Yeniretnowati, Tri Astuti; Perangin Angin, Yakub Hendrawan (Sekolah Tinggi Teologi Parakletos Tomohon, 2023)
Abstract: This research is focused on formulating discipleship strategies in the spiritual development of ASN Christians, so that in their work they can have an impact to contribute to building the community, region, nation and carrying out God's mission calling according to the field of duty and work. The method in this study uses qualitative methods (grounded research). The process began with establishing a theoretical framework, creating research questions, interviewing informants (7 people), recapitulating the results of the interviews, conducting analysis, comparing the results of interviews with ASN KTB participants that the researchers had formed and carrying out the KTB for 2 to 4 months as many as 4 people. The results of the study show that: First, Discipleship is very important to be carried out in Christian ASN as a strategy for spiritual development, discipleship must be immediately developed in a Christian ASN environment oriented towards the main goal of serving God through the calling of work that God bestows and continue to strive to maintain commitment together - together so as to achieve the goal of implementing the discipleship. Second, the strategy for overcoming obstacles in the ASN KTB so that it can continue until the goal is achieved. Third, the Christian ASN KTB has a sizable positive impact both as an increase in the maturity of personal spirituality, improving performance in the organization and increasing dedication and service to the community, country and to God, which have been felt by the participants of the Christian ASN KTB that have been running. Fourth, Christian ASN KTB discipleship methods can be carried out in various ways through various methods.Abstrak: Penelitian ini difokuskan pada perumusan strategi pemuridan dalam pembinaan spiritual ASN Kristiani, sehingga dalam pekerjaannya dapat memberikan dampak untuk berkontribusi dalam membangun masyarakat, daerah, bangsa serta menjalankan panggilan misi Allah sesuai bidang tugas dan pekerjaannya. Metode dalam penelitian ini menggunakan metode kualitatif (grounded research). Prosesnya dimulai dengan menetapkan kerangka teori, membuat pertanyaan penelitian, wawancara dengan informan (7 orang), merekap hasil wawancara, melakukan analisis, membandingkan dengan hasil wawancara dari peserta KTB ASN yang telah peneliti bentuk dan melaksanakan KTB selama 2 sampai 4 bulan sebanyak 4 orang. Hasil penelitian menunjukkan bahwa: Pertama, Pemuridan sangat penting untuk dilaksanakan pada ASN Kristiani sebagai strategi pembinaan spiritual, pemuridan harus segera dikembangkan di lingkungan ASN Kristiani dengan berorientasi kepada tujuan utama untuk melayani Tuhan melalui panggilan pekerjaan yang Tuhan anugerahkan dan terus berupaya mempertahankan komitmen bersama – sama sehingga tercapai tujuan dari pelaksanaan pemuridan tersebut. Kedua, Strategi untuk mengatasi kendala dalam KTB ASN agar dapat terus berjalan sampai tercapainya tujuan. Ketiga, KTB ASN Kristiani memberikan dampak positif yang cukup besar baik sebagai peningkatan pendewasaan spiritualitas pribadi, meningkatkan kinerja dalam organisasi serta peningkatan pengabdian dan pelayanan kepada masyarakat, negara dan kepada Tuhan, telah dirasakan oleh para peserta KTB ASN Kristiani yang telah berjalan. Keempat, Metode pemuridan KTB ASN Kristiani dapat dilakukan secara bervariasi melalui berbagai metode.